PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT KEMAMPUAN KELUARGA DALAM PERAWATAN HALUSINASI DI RUMAH SAKIT JIWA Prof.Dr.V.L. RATUMBUYSANG MANADO - Verra Karame; Esther Lontoh; Gloria I Mamangkey (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Hallucinations are a point where a person cannot distinguish between the real world and their subconscious world. Support from various parties must be obtained for patients with hallucinations to support the process of controlling these hallucinations, the most important thing is of course from the family where the role of the family in the process of caring for patients with hallucinations needs to be considered. To determine the effect of health education on the level of family ability in treating hallucinations. This study uses a quantitative research type with a Quasy experimental design. The design used in this study is One Group Pre Post Design. The study population was all hallucination patients who were admitted to the Prof. Dr.V.L Ratumbuysang Manado Mental Hospital Polyclinic totaling 97 people, the number of samples was 15 respondents, the measuring instrument used was a questionnaire. In the results of the study using the Wilcoxon Sign Rank Test statistical test between before and after showing PValue = 0.00 <0.05. This means that there is a significant influence between the provision of health education on changes in the level of family ability in treating hallucinations. The method provided in the study can be a reference for families to maintain their ability in treating hallucinations and health workers can provide health education on how to treat hallucinations correctly periodically to families to improve knowledge and ability in treatment.